Dynamic Parameter Determination on Simple Supported Beam Using OMA (Proceedings of Faculty of Civil Engineering, 2019)
This paper presents dynamic analysis of rectangular hollow section 30 x 50 x 3.2 mm steel beam of 3.0 m in length with the aim of determining the values of the dynamic parametres (modal frequencies, modes and modal damping) using the method of operational modal analysis. The main advantage of this method in comparison to the experimental modal analysis is the ability of getting modal parameters of a test experimental modal analysis is the ability of getting modal parameters of a test object without knowing the excitation. For the validation of experimental results, a numerical model was constructed in STAAD.Pro. The excitation on the test object was made in one specified point, and the dynamic output of the beam was measured using uniaxial accelerometers with sensitivity of 100 mV/g, which were placed in several characteristic points. Data acquisition and their analysis was conducted using vibration analysis software ModalVIEW. In some measurements, the principle of interpolation points between the measured points (points with accelerometers) has been used. Measuring the response to the excitation frequencies fi, modes and modal damping ξi were acquired (i = 1, 2,..., n where n represents the number of modes). Frequencies and modes obtained experimentally were compared to the frequencies and modes calculated on a numerical model of the beam.
Keywords: operational modal analysis; modes; frequency; damping